1965
DOI: 10.1126/science.148.3669.524
|View full text |Cite
|
Sign up to set email alerts
|

Nematodes: Biological Control in Rice Fields: Role of Hydrogen Sulfide

Abstract: In flooded rice fields a decline in total nematode populations began shortly after the onset of soil anaerobiosis and was correlated with a sustained increase in concentration of molecular hydrogen sulfide in the soil-water phase. Laboratory tests showed that hydrogen sulfide at concentrations found in flooded fields killed 100 percent of nematodes in 5 to 10 days. The effect of hydrogen sulfide and its pattern of occurrence in the soils of water-saturated rice fields suggest that this compound can be a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

1975
1975
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(17 citation statements)
references
References 6 publications
0
16
0
1
Order By: Relevance
“…Several substances, e.g. ammonia, H 2 S, formaldehyde, fatty acids, amino acids, phenols etc., released during decomposition of organic matter are toxic to many plant parasitic nematodes (Rodriguez-Kabana et al, 1965;Alam et al, 1978). Metabolites of microbes, which are activated by organic amendments, are toxic to plant-parasitic nematodes (Alam et al, 1973;Pandey and Singh, 1990).…”
Section: Resultsmentioning
confidence: 98%
“…Several substances, e.g. ammonia, H 2 S, formaldehyde, fatty acids, amino acids, phenols etc., released during decomposition of organic matter are toxic to many plant parasitic nematodes (Rodriguez-Kabana et al, 1965;Alam et al, 1978). Metabolites of microbes, which are activated by organic amendments, are toxic to plant-parasitic nematodes (Alam et al, 1973;Pandey and Singh, 1990).…”
Section: Resultsmentioning
confidence: 98%
“…Johnson (1959) reported toxicity of culture filterates of Clostridium butyricum containing formic, acetic, propionic and butyric acids to Tylenchorhynchus martini. Rodriguez-Kabana et al (1965) found Desulfovibrio desulfurieans responsible for producing hydrogen sulphide in adequate amounts to control nematodes in flooded rice fields.…”
Section: Bacterial Biocontrol Agentsmentioning
confidence: 99%
“…Increased microbial activity in amended soil causes enhanced enzymatic activities Kokalis-Burelle and Rodriguez-Kabana 1994) and the accumulation of end-products and metabolites of microbes which may be nematicidal (Mankau and Minteer 1962;Rodriguez-Kabana et al 1965;Badra et al 1979).…”
Section: Role Of Organic Amendmentsmentioning
confidence: 99%
“…Addition of organic matter to soil stimulates activity of microorganisms, resulting in increased soil enzymatic activities and the accumulation of certain nematicidal compounds (Badra et al, 1979, Rodrfguez-K~fbana andHollis, 1965;Rodrfguez-K~ibana et al, 1987). Types of organic amendments used to control plant parasitic nematodes include crop debris, oil cakes, animal waste, and industrial by-products (Mian and Rodrfguez-K~ibana, 1982a).…”
Section: Introductionmentioning
confidence: 97%